Effect of K2SO4 and KNO3 Foliar Application on Wheat Growth: Foliar Application Effect on Wheat Growth - Arshadullah, Muhammad; Ali, Arshad; Hyder, Syed Isthiaq; Mahmood, Imdad Ali; Zaman, Badar-uz- (Biological Sciences - PJSIR, 2015)
A field experiment was conducted to investigate the effect of different concentrations of K2SO4 and KNO3 foliar application (2 and 4%) on the growth of wheat (cv. Watan) at Soil Salinity Research Institute (SSRI) farm, Pindi Bhattian, Punjab, Pakistan during Rabi season, 2007. Treatments were: soil application K2SO4 , KNO3, 2 and 4% K2SO4, 2% KNO3 + 2% K2SO4, 4% KNO3 +2% K2SO4, 2% KNO3 + 4% K2SO4 ,4% KNO3+4% K2SO4 . Treatments were assigned using randomised complete block design with three replications. The crop was harvested at maturity, data on tillering, plant height, spike length, number of grains/spike, 1000-grain weight, straw and wheat yields were recorded. Tillering, number of grains/spike, 1000-grain weight and wheat yield significantly (P £ 0.05) increased by different levels of doses. 2% K2SO4 and 4% K2SO4 improved the tillering capacity of wheat compared with the control. The combination of 2% KNO3 + 4% K2SO4 attained the highest grain yield (2825 kg/ha) which was statistically at par with 2% K2SO4 (2795 kg/ha). The lowest grain yield (2129 kg/ha) was received by the control (soil applied K2SO4). Grain yield after spraying was up to 31% higher than in the control.